Influence of an audience-oriented task, executive function, and trait perspective taking on EFL writing - Coşkun, Turgut. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
This study adopted a cognitive approach and investigated the effect of an audienceoriented task on the passages composed by novice EFL writers by considering their executive function and trait perspective-taking capabilities. With this purpose, the writing performance of two groups assigned to either an experimental or a control condition was compared. The audience- oriented experimental group was exposed to a writing task that emphasized the audience. Most importantly, they were asked to read three short messages shared by their audience, then take their perspective and write down whatever came to their minds. The non-audience-oriented control group was also asked to read the messages but was not encouraged to take the audience's perspective. They were just asked to write down whatever came to their minds. Following that, both groups wrote the main passages and completed four executive function tasks and a trait perspective-taking scale. The results revealed that exposing upper-intermediate novice EFL writers to an audience- oriented task increased the overall writing quality of the participants with high executive function or trait perspective- taking capabilities. Regarding the level of persuasiveness, the task's effect may depend on the availability of sufficient executive function resources. These findings confirm the importance of a task for directing and managing cognitive resources and show the executive function's central role and trait perspective-taking’s importance in writing. The tasks that encourage employing these individual resources may enrich the instructor toolboxes.
Keywords: Reading -- Remedial teaching.; English language -- Writing -- Programmed instruction.; EFL writing.; Reader-oriented writing.